E-Mail-Austausch zwischen Raabe Eva und Katharina Greven - Raabe, Eva; Greven, Katharina (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2015)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Artists; Wood-carving; Email; Papua New Guinea; New Guinea; Port Moresby; Yoruba Art; Art Collector; Art Collecting